Primary carcinoid tumor of the gallbladder: A case report and brief review of the literature - Liu Hao-Run; Li Wei-Min; Zou Yi-Ping; Li Ning (World Journal of Surgical Oncology, 2010)
Abstract Background Primary carcinoid tumor of the gallbladder is rare and comprises less than 1% of all carcinoid tumors. Preoperative diagnosis of carcinoid tumor of the gallbladder is difficult. The imageology findings are similar to those in other gallbladder cancers. Case presentation A 46-year-old woman was hospitalized with a preoperative diagnosis of gallbladder carcinoma, The patient was referred for surgical opinion and laparotomy was subsequently performed. A 4 × 5 cm mass was found within the gallbladder, located on the free surface of the body and fundus of the gallbladder. Neither metastases nor direct invasion to the liver was found. The entire mass and gallbladder were excised and intact. Histologically, the tumor consisted of small oval cells with round-to-oval neclei and tumor cells formed small nodular, trabeculare and acinar structures. The tumor showed moderate pleomorphism with scattered mitotic figures, but no definite evidence of vascular permeation, perineural invasion or lymphatic permeation was seen. The tumor cells invaded the mucosa extensively, and some penetrated the muscular layer but not through the serosa of the gallbladder into the liver. Immunohistochemical studies revealed strong positive reaction for chromogranin A and NSE. This lesion was proved to be a primary carcinoid tumor of the gallbladder. A brief review of literature, clinical feature, pathology and treatment of this rare disease was discussed. Conclusion Primary carcinoid tumor of the gallbladder is uncommon. The definite diagnosis is often made on histopathological results after surgery.